Assessing Structural Correlations and Heterogeneity Length Scales in Functional Porous Polymers from Physical Reconstructions. (28th August 2015) - Müllner, Tibor; Zankel, Armin; Lv, Yongqin; Svec, Frantisek; Höltzel, Alexandra; Tallarek, Ulrich
<x xml:space="preserve">Abstract</x> A general, model‐free, quantitative approach to the key morphological properties of a porous polymer monolith is presented. After 3D reconstruction, image‐based analysis delivers detailed spatial and spatially correlated information on the structural heterogeneities in the void space and the polymer skeleton. Identified heterogeneities, which limit the monolith's performance in targeted applications, are traced back to the preparation process.